Student’s Perception Towards the Use of DeepL Translator in Writing Thesis or Journal for English Education Students - Asmara, Devi Sunita Mutia; Kembaren, Farida Repelitawati Br (IJLECR (International Journal of Language Education and Cultural Review), 2024)
Translation is a crucial aspect for non-native English students, especially when writing academic theses or journals. This study aims to discuss the use of the DeepL Translator application in writing a thesis or journal of English students. This research employs qualitative methods with a case analysis design by analyzing data derived from questionnaire data and deeper interviews related to the use of DeepL Translator. The use of questionnaire data and further interviews were conducted with 24 final semester English students. The data were analyzed using Miles and Huberman’s techniques, which include data reduction, data presentation, data display, and drawing conclusions to evaluate the effectiveness of the DeepL Translator. The results of this study show that students use DeepL translators a lot when making their theses or journals. By using the method of translating per paragraph, students complete their thesis or journal using DeepL Translator to convert Indonesian into English. The reason they use this application is because the results of this translation are more accurate and effective than those of other translation machines and also the students agree that they are often use this DeepL Translator to write their thesis or journal.